Electrolyte additive composition containing novel lithium salt and application thereof
By using the additive composite lithium salt and polyphonic compounds in lithium -ion battery electrolytes to solve the high temperature storage stability and gas expansion of lithium -ion batteries at high voltage and ultra -high temperature at high voltage and high temperature , Achieve higher cycle stability and dynamic performance.
Patent Information
- Application Number
- CN202310883893.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-19
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2043-07-19
AI Technical Summary
In high voltage and ultra-high temperature scenarios, lithium-ion batteries face the problems of poor high-temperature storage stability and gas production expansion, and it is difficult to take into account low impedance and long-cycle stability.
An additive composition containing boron trifluoride complex lithium salt of pyrosulfate and polynitrile compounds is used to form a stable passivation film on the negative electrode interface through the first additive, and the second additive combines with the positive surface active sites to inhibit the electrolyte Decomposition and resistance growth.
It significantly improves the high-temperature cycle stability and high-temperature storage stability of lithium-ion batteries under high voltage, suppresses gas expansion, reduces initial impedance, and improves the battery's dynamic performance and long-term cycle stability.
Smart Images

Figure CN119340477A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of lithium ion battery electrolyte, and in particular to an additive composition comprising pyrosulfate boron trifluoride composite lithium salt and polynitrile compounds, and application of the additive composition in electrolyte preparation, and application of the prepared electrolyte in lithium ion batteries. Background Art
[0002] In the past nearly three decades, consumer electronics (3C) have achieved unprecedented success. Lithium cobalt oxide has become the most widely used positive electrode material in 3C lithium-ion batteries, and its high volume energy density is its greatest competitiveness. Improving the positive electrode voltage of lithium cobalt oxide and developing high-voltage electrolytes are the basic routes for the development of high-end digital batteries. At the beginning of 2013, the charging cut-off voltage of mass-produced LCO batteries in the lithium battery industry was generally 4.2V. By 2019, the charging cut-off voltage of mass-produced LCO batteries was generally 4.45V. In the next five years, it is planned to mass-produce battery systems of 4.52V or even higher. The seemingly small increase in the positive electrode working voltage of 0.15-0.25V requires the technical accumulation and progress behind it, but it requires continuous technical optimization of positive electrode materials and electrolytes, including how to suppress high-temperature gas expansion, improve cycle life, and take into account low-temperature performance. The electrolyte plays an important role in this. At a high charging voltage, lithium cobalt oxide batteries undergo a transformation from hexagonal phase to monoclinic phase. This transformation causes the following side reactions in the electrolyte: (1) The interface stability of the positive electrode deteriorates, the number of highly oxidative active sites increases, and the electrolyte decomposes oxidatively; (2) The positive electrode is accompanied by an oxygen evolution reaction, and oxygen participates in charge transfer to further oxidize the electrolyte; (3) The positive electrode transition metal, especially cobalt, dissolves, catalyzing the decomposition of the negative electrode SEI film, causing the electrolyte to repair and produce gas, and increasing impedance. In response to the above technical difficulties, the research on high-voltage electrolytes mainly focuses on the development of electrolyte additives and the optimization and adjustment of the formula.
[0003] In order to improve the comprehensive performance of batteries under high voltage, lithium salt compounds such as borates and phosphates are widely used in lithium-ion battery electrolytes due to their excellent positive and negative electrode film-forming functions to improve the long cycle life of battery cells.
[0004] Qingyu Dong et al. (ACS Appl. Energy Mater. 2020, 3, 695-704) disclosed that LiDFOB can stabilize the NCM811 electrode interface, reduce polarization, and improve cycle performance. However, LiDFOB containing oxalate structure is prone to produce CO during high temperature and long cycle storage. 2 Gases such as these can easily cause problems such as swelling of soft-pack batteries, reducing safety of use and battery life.
[0005] Zhuhai Guanyu patent CN110148784A discloses the use of a combination of fluorinated cyclic carbonate, nitrile compounds, lithium difluorophosphate and tetravinylsilane as additives to enable the battery to have both high and low temperature performance. However, lithium difluorophosphate has low solubility in conventional ester solvents, which will bring certain difficulties to the production of electrolyte formulations.
[0006] In addition, sulfate additives (such as vinyl sulfate, DTD) and fluorocarbonate additives (such as fluoroethylene carbonate, FEC) are often used in the electrolyte industry to improve the performance of batteries under high voltage. However, DTD has poor thermal stability, is prone to discoloration during storage, and increases the acidity of the electrolyte. In an electrolyte with lithium hexafluorophosphate as the main salt, FEC will produce HF during high-temperature storage, which has a negative effect on the high-voltage positive electrode and causes a sharp increase in gas production during high-temperature storage.
[0007] Pyrosulfate boron trifluoride composite lithium salt is a new electrolyte additive developed by Zhejiang Chemical Research Institute Co., Ltd. Its patent CN202211583064.X discloses that the additive can improve the battery's cycle performance, high-temperature storage performance and low-temperature performance. At the same time, patent CN202211583043.8 also discloses the use of pyrosulfate boron trifluoride composite lithium salt, vinyl sulfate and / or 1,3-propane sultone in combination, or the further addition of vinylene carbonate in combination, so that lithium-ion batteries still have excellent cycle performance, high-temperature storage performance and the effect of inhibiting battery gas production under high energy density systems, and can also inhibit the impedance growth during the battery cycle and further improve the low-temperature performance. However, in high-voltage working environments, especially when the positive electrode working voltage is ≥4.45V, although lithium salt additives have the advantages of reducing impedance and improving circulation, the battery system still faces the difficulty of poor stability in high-voltage and high-temperature storage, especially under ultra-high temperature conditions of 85°C. The gas production of the battery increases after high-temperature storage. This is a technical difficulty that is difficult to take into account while taking into account the technical requirements of low impedance for high-voltage battery systems.
[0008] Therefore, it is also an important research topic to continue in-depth research to develop more stable, safe and environmentally friendly pyrosulfate boron trifluoride complex lithium salt compositions and electrolyte formulas to meet the battery performance requirements under high voltage and 85°C ultra-high temperature scenarios. Summary of the invention
[0009] The chemical names of the various compound codes involved in the present invention are explained as follows:
[0010] 1. LiDFOB, chemical name: lithium difluorooxalate borate;
[0011] 2. LiPO 2 F 2 , chemical name: lithium difluorophosphate;
[0012] 3. PS, chemical name: 1,3-propane sultone;
[0013] 4. TVS, chemical name: tetravinylsilane (CAS: 1112-55-6);
[0014] 5. HTCN, chemical name: 1,3,6-hexanetrinitrile;
[0015] 6. ADN, chemical name: adiponitrile;
[0016] 7. SN, chemical name: succinonitrile;
[0017] 8. TCP, chemical name: 1,2,3-tri(cyanoethoxy)propane;
[0018] 9. DFEA, chemical name: 2,2-difluoroethyl acetate (CAS: 1550-44-3);
[0019] 10. MMDS, chemical name: methylene disulfonate;
[0020] 11. DTD, chemical name: vinyl sulfate.
[0021] In order to solve the above technical problems, the present invention further proposes an additive composition comprising pyrosulfate boron trifluoride complex lithium salt and a nitrile compound and its application in electrolyte preparation and lithium ion batteries. The additive composition can further improve the high-temperature cycle stability and high-temperature storage stability of lithium ion batteries under high voltage on the basis of maintaining the high and low temperature performance of pyrosulfate boron trifluoride complex lithium salt, especially inhibit the gas production and expansion of the battery under high temperature conditions, and reduce the initial impedance of the battery.
[0022] The objective of the present invention is achieved through the following technical solutions:
[0023] An electrolyte additive composition containing a novel lithium salt, the additive composition comprising:
[0024] The first additive comprises at least a novel lithium salt having a structure represented by the following formula (I-1):
[0025]
[0026] The second additive is a nitrile compound selected from the structure represented by the following formula (II), and the nitrile compound is a polynitrile compound:
[0027]
[0028] Where M 1 is selected from -CH, P or -P=O, n is selected from an integer of 0 to 5; R1 , R 2 , R 3 are independently selected from a direct bond, oxygen, -R 4 -、-OR 4 -or-R 5 -OR 4 -, where R 4 , R 5 Independently selected from C1-C5 alkylene, C2-C5 alkenylene, or C1-C5 alkylene, C2-C5 alkenylene substituted by C1-C3 alkyl or cyano;
[0029] The mass ratio of CN functional groups in the first additive to the second additive is 0.03-4.0; preferably, the mass ratio of CN functional groups in the first additive to the second additive is 0.08-1.0; more preferably, the mass ratio of CN functional groups in the first additive to the second additive is 0.1-0.3.
[0030] The mass ratio of the CN functional groups in the first additive and the second additive of the present invention refers to: the ratio of the mass content of the first additive in the electrolyte to the mass content of the CN functional groups in the second additive in the electrolyte. The mass content of the first additive in the electrolyte = (mass of the first additive / total mass of the electrolyte) * 100%; the mass content of the CN functional groups in the second additive in the electrolyte = (mass of the second additive * mass content of the CN functional groups in the second additive / total mass of the electrolyte) * 100% = mass content of the second additive in the electrolyte * mass content of the CN functional groups in the second additive. The mass content of the CN functional groups in the second additive is calculated by the following formula:
[0031]
[0032] Wherein, i = 1, 2, ..., n, n represents the number of different nitriles, 1 ≤ n ≤ 10, M i is the relative molecular mass of different nitriles, a i is the number of CN functional groups of the i-th nitrile, and 26 is the relative molecular mass of the CN functional group. For example, if the second additive contains only one nitrile compound, and the nitrile compound contains two CN functional groups, then n is 1, and the relative molecular mass of the nitrile compound is M 1 The mass content of CN functional group in the second additive is 52 / M 1 For another example, the second additive contains two different nitrile compounds, the first nitrile compound contains two CN functional groups, and the relative molecular mass is M 1 The second nitrile compound contains three CN functional groups and has a relative molecular mass of M 2 , then n is 2,
[0033]
[0034] In commercial high-voltage electrolyte formulations, the composition of nitrile compounds is usually composed of 2-4 second additives, and different nitrile compounds have different numbers of CN functional groups. Therefore, using the mass content of CN functional groups instead of the mass content of nitrile compounds can more reasonably express the synergistic effect of the first additive and the second additive.
[0035] In the additive composition of the present invention, the first additive can form a stable passivation film at the negative electrode interface before the second additive when it is first formed, inhibiting the second additive (polycyano additive) from damaging the negative electrode interface and reducing the negative electrode impedance. In this way, the second additive can also be promoted to rely on the strong coordination ability of its cyano (CN) functional group to combine with the active sites on the positive electrode surface (such as high-valent metal ions such as nickel / cobalt / manganese, etc.), which plays a role in shielding the active ions on the positive electrode surface and reducing the decomposition of the electrode to the electrolyte; and the nitrogen triple bond energy in the cyano (CN) functional group in the second additive is very high, not easily oxidized, and has strong stability on the high-voltage positive electrode. By using the first additive and the second additive together, the flatulence of the lithium-ion battery under high-temperature storage is suppressed, the negative electrode impedance is reduced, the dynamic performance of the battery is improved, and the long-cycle stability of the lithium-ion battery is guaranteed.
[0036] During the preparation process of the first additive of the present invention, due to different preparation processes, in addition to the novel lithium salt having the structure shown in the above-mentioned (I-1), at least one of the compounds shown in the following formulas (I-2), (I-3), (I-4), (I-5), and (I-6) may be included:
[0037]
[0038]
[0039] The first additive contains at least 80 wt % or more of the novel lithium salt having the structure represented by formula (I-1). Preferably, the first additive contains 80.0 to 95.0 wt % of the novel lithium salt having the structure represented by formula (I-1), and the rest is at least one of compounds (I-2), (I-3), (I-4), (I-5) or (I-6).
[0040] In the second additive, M 1 is selected from -CH, P or -P=O, n is selected from an integer of 0 to 3; R 1 , R 2 , R 3 are independently selected from a direct bond, oxygen, -R 4 -、-OR 4-or-R 5 -OR 4 -, where R 4 , R 5 Independently selected from C1-C3 alkylene, C2-C3 alkenylene, or C1-C3 alkylene, C2-C3 alkenylene substituted by C1-C3 alkyl or cyano.
[0041] Furthermore, the second additive is selected from at least one of the nitrile compounds shown in the following structures:
[0042]
[0043] The present invention also provides a method for preparing an electrolyte, the method comprising: adding a main lithium salt to a non-aqueous solvent until the main lithium salt accounts for 8 to 20 wt% of the total mass of the electrolyte, and then adding any of the above-mentioned additive compositions to obtain an electrolyte, and making the first additive account for 0.01 to 5.0 wt% of the total mass of the electrolyte, and the second additive account for 0.1 to 10 wt% of the total mass of the electrolyte; further preferably, making the first additive account for 0.01 to 2.0 wt% of the total mass of the electrolyte, and the second additive account for 1 to 8 wt% of the total mass of the electrolyte; more preferably, making the first additive account for 0.1 to 1.0 wt% of the total mass of the electrolyte, and the second additive account for 2 to 6 wt% of the total mass of the electrolyte.
[0044] The non-aqueous solvent is selected from a mixture of cyclic carbonates and linear carbonates and / or linear carboxylates, wherein the cyclic carbonate is selected from at least one of ethylene carbonate, propylene carbonate or fluoroethylene carbonate; the linear carbonate is selected from at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate or methyl trifluoroethyl carbonate; the linear carboxylate is selected from at least one of ethyl acetate, ethyl propionate, propyl propionate, 2,2-difluoroethyl acetate or 2,2,2-trifluoroethyl acetate, and the amount of any non-aqueous solvent is 0.1-50wt% of the total mass of the electrolyte;
[0045] The main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.
[0046] In the preparation method of the electrolyte of the present invention, a third additive is further added, and the third additive is selected from at least one of the sulfur-oxygen double bond compounds shown in the following structure, and the amount of the third additive accounts for 0.5 to 5.0 wt% of the total mass of the electrolyte:
[0047]
[0048] The third additive containing sulfur-oxygen double bonds can form a film on the surface of the positive and negative electrodes. The formed alkyl lithium sulfate containing tetravalent or hexavalent high-valent states can improve the oxidation resistance of the positive electrode interface and has high lithium ion conductivity. It cooperates with the above-mentioned first additive to form an organic-inorganic composite SEI film. Especially when the mass ratio of the CN functional groups in the first additive and the second additive is lower than 1.0, the introduction of the third additive can more effectively inhibit the damage of the second additive to the negative electrode interface film and improve the storage and cycle performance of the battery.
[0049] Preferably, the amount of the third additive is 1.0-4.0 wt % of the total mass of the electrolyte.
[0050] According to the application scenarios of different electrolytes and the requirements of battery electrochemical performance, in the preparation method of the electrolyte of the present invention, a basic additive is further added, and the basic additive is selected from at least one of fluoroethylene carbonate, vinylene carbonate, lithium difluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorobisoxalatophosphate, tris(trimethylsilyl)phosphate, and tris(trimethylsilyl)borate, and any addition amount accounts for 0.1 to 2.0 wt% of the total mass of the electrolyte.
[0051] As the cut-off operating voltage of lithium-ion batteries increases, higher challenges are posed to high-temperature storage performance at higher temperatures (such as 85°C). Therefore, further, in the preparation method of the electrolyte of the present invention, a fourth additive is further added, and the fourth additive is selected from at least one of tetravinylsilane, 2,4,6-tri(allyloxy)-1,3,5-triazine, 1,3,5-triallyl isocyanurate, 1,3-dioxane, and 1,4-dioxane, and any addition amount accounts for 0.1-2.0wt% of the total mass of the electrolyte, which is used for positive electrode film formation, inhibiting gas production, and improving the high-temperature storage performance of the battery at 85°C.
[0052] The present invention also provides a lithium ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator. In particular, the lithium ion secondary battery is prepared by the following method:
[0053] The positive electrode sheet, the separator and the negative electrode sheet are wound together into a roll core, sealed with an aluminum-plastic film and then baked, and then the electrolyte prepared by any of the above-mentioned preparation methods is injected into it, and a lithium-ion secondary battery is obtained after standing, forming, volume separation and aging.
[0054] The active material of the positive electrode plate of the lithium secondary battery is selected from lithium cobalt oxide, lithium nickel manganese oxide, lithium-rich manganese base, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate or LiNi x Co y Mn z L (1-x-y-z) O 2, wherein L is Al, Sr, Mg, Ti, Ca, Zr, Zn, Si, W or Fe, 0≤x≤1, 0≤y≤1, 0≤z≤1, 0.5≤x+y+z≤1, and the active material of the negative electrode plate is selected from graphite, silicon carbon or silicon oxygen material.
[0055] Preferably, the active material of the positive electrode plate contains at least LiCoO2. That is, the active material of the positive electrode plate is LiCoO2, or LiCoO2 and LiNi x Co y Mn z L (1-x-y-z) O 2 of composite materials.
[0056] The electrolyte prepared by using the additive composition of the present invention is suitable for lithium ion secondary batteries with a cut-off voltage of ≥4.35 V, and is also suitable for lithium ion secondary batteries with a cut-off voltage of ≥4.45 V, and is more suitable for lithium ion secondary batteries with a cut-off voltage of ≥4.48 V. In the advantageous electrolyte formula of the present invention, when it is used in a high voltage environment with a cut-off voltage of 4.48 V, the high temperature cycle stability, high temperature storage stability and low temperature performance of the battery are still maintained.
[0057] The electrolyte additive of the present invention participates in the construction of the electrode / electrolyte interface during the battery formation process, so that in the electrolyte liquid of the lithium ion secondary battery, the first additive accounts for 0.01-2.0wt% of the total mass of the electrolyte liquid, and the second additive accounts for 0.1-6.0wt% of the total mass of the electrolyte liquid.
[0058] Furthermore, the third additive accounts for 0.1-3.0 wt % of the total mass of the electrolyte liquid, and the fourth additive accounts for 0.02-1.5 wt % of the total mass of the electrolyte liquid.
[0059] Compared with the prior art, the present invention has the following beneficial effects:
[0060] The additive composition of the present invention, based on the specific ratio and specific respective contents of the CN functional groups in the first additive and the second additive, synergistically inhibits the flatulence of the lithium-ion battery under high-temperature storage, reduces the negative electrode impedance, improves the dynamic performance of the battery, and ensures the long-cycle stability of the lithium-ion battery. Compared with conventional lithium salt additives on the market, the additive composition has a significantly better inhibitory effect on high-temperature storage gas production than the combination of nitrile compounds and lithium oxalate salt additives such as LiDFOB and LiDFOP. DETAILED DESCRIPTION
[0061] The present invention is further described below in conjunction with specific embodiments, but the present invention is not limited to these specific embodiments. Those skilled in the art should recognize that the present invention covers all possible alternatives, improvements and equivalents within the scope of the claims.
[0062] In the embodiments and comparative examples of the present invention, the types of the first additive include the following:
[0063] The first additive A1: contains 95 wt% of compound I-1 and 5 wt% of compound I-2;
[0064] The first additive A2 contains 90 wt % of compound I-1, 6 wt % of compound I-2 and 4 wt % of compound I-3.
[0065] 1. Preparation of electrolyte
[0066] In a glove box filled with argon (water content <5 ppm, oxygen content <10 ppm), ethylene carbonate (EC), propylene carbonate (PC), propyl propionate (PP), diethyl carbonate (DEC), and fluoroethylene carbonate (FEC) were mixed in a mass ratio of 1.5:1.5:3:1:1 to form an organic solvent, and LiPF was added based on the total mass of the electrolyte. 6 The mass percentage is 14%, and it is used as the basic electrolyte M.
[0067] The first additive, the second additive and other additives are quantitatively added to the above-mentioned basic electrolyte M, and mixed evenly to form an electrolyte, wherein the mass ratio of the CN functional groups in the first additive and the second additive is recorded as a, and the mass content of the CN functional groups in the second additive is recorded as CN%. The specific electrolyte formula is shown in Table 1 below:
[0068] Table 1 High voltage electrolyte formula Table 1
[0069]
[0070]
[0071]
[0072] 2,2-difluoroethyl acetate (DFEA), the first additive, the second additive and other additives are quantitatively added to the basic electrolyte M and mixed evenly to form an electrolyte. The specific electrolyte formula is shown in Table 2 below:
[0073] Table 2 High voltage electrolyte formula Table 2
[0074]
[0075] 2. Electrochemical performance test
[0076] The electrolyte formula adopted by the present invention solves the problem of poor interface stability of high-voltage positive electrode electrolyte by using the first additive and the second additive together, and at the same time improves the compatibility of nitrile compounds with the negative electrode interface, and is suitable for lithium cobalt oxide / graphite, lithium cobalt oxide / silicon carbon, ternary / graphite, ternary / silicon carbon, lithium iron manganese phosphate / graphite and other systems. This embodiment only selects the lithium cobalt oxide / graphite system for performance testing.
[0077] The lithium-ion battery electrolytes of the above embodiments and comparative examples were respectively loaded into soft-pack lithium-ion batteries with a capacity of 1000 mAh. The lithium-ion power battery comprises a positive electrode sheet, a negative electrode sheet, a separator, an electrolyte and battery auxiliary materials. The positive electrode active material is LiCoO 2 , the negative electrode active material is graphite.
[0078] The preparation process is as follows: the positive electrode sheet, the separator and the negative electrode sheet are wound together into a core, which is sealed with an aluminum-plastic film and then baked so that the moisture content of the electrode meets the requirements. After baking, the battery cell is injected with electrolyte, and the finished soft-pack battery cell is obtained through the steps of standing, forming, capacity separation and aging.
[0079] The above lithium-ion batteries are tested for various performances, including:
[0080] (1) Cyclic performance test
[0081] At the specified temperature, charge at a constant current of 1C to the charge cut-off voltage (4.50V, the same below), then charge at a constant voltage until the current drops to 0.1C, then discharge at a constant current of 1C to the discharge cut-off voltage (3.0V, the same below), and repeat this cycle for a specific number of weeks. Record the discharge capacity of the first week and the discharge capacity of the last week, and calculate the capacity retention rate of the battery cycle as follows:
[0082] Capacity retention rate = discharge capacity in the last week / discharge capacity in the first week*100%.
[0083] (2) 85℃ high temperature storage performance test
[0084] At room temperature, the battery was charged at a constant current of 1C to the charge cut-off voltage, and then charged at a constant voltage until the current dropped to 0.1C, and then stored in a constant temperature oven at 85°C for 12 hours. The volume change rate and capacity recovery rate before and after high-temperature storage were recorded.
[0085] (3) -20℃ low temperature discharge capacity
[0086] At room temperature, charge at a constant current of 0.5C to the charge cut-off voltage, then charge at a constant voltage until the current drops to 0.1C, then discharge at a constant current of 0.5C at -20°C to the discharge cut-off voltage, and record the discharge capacity at low temperature. Low temperature capacity retention rate = discharge capacity at low temperature / discharge capacity in the first week * 100%.
[0087] (3) Initial ACR impedance
[0088] At room temperature, the battery capacity was adjusted to 50% SOC (state of charge) with a standard charging current, and the internal resistance (mΩ) at a frequency of 1KHz was tested at the fixed ear position of the lithium battery after capacity division using a Japanese Hioki internal resistance meter, which was recorded as the initial ACR impedance (AC internal resistance).
[0089] The test results are shown in Table 3 below:
[0090] Table 3 LCO / AG-4.5V electrochemical test results (4.50V-3.0V)
[0091]
[0092]
[0093]
[0094] According to the data in Table 3 above, by comparing Example 2 with Comparative Examples 1 to 2, it can be seen that the combined use of the first additive and the second additive, compared with the use of either alone, can inhibit the gas expansion of the battery cell after storage at ultra-high temperature of 85°C for 12 hours in a lithium cobalt oxide high voltage system and improve the capacity recovery rate of the battery, while effectively improving the -20°C low temperature discharge performance of the battery cell and the high voltage and high temperature cycle performance.
[0095] Further comparison of Examples 19 to 22 and Comparative Examples 4 to 7 shows that the mass ratio of the CN functional groups in the first additive and the second additive is in the range of 0.03 to 4.0, and the addition amount of the first additive in the electrolyte satisfies 0.05 to 5.0 wt%, and the second additive satisfies 0.5 to 10 wt%. The high-temperature storage and cycle performance of the battery under high voltage are effectively improved, and the battery has a relatively good low-temperature discharge capacity of -20°C. At the same time, when preparing the electrolyte of Comparative Example 7, when the SN content of the second additive reaches 12%, a small amount of white crystals appear in the electrolyte. This is due to the fact that LiPF 6 The reaction with SN further proves that the content of the second additive is not more than 10.0wt%. Further comparing Examples 26 to 29, the mass ratio of the CN functional groups in the first additive and the second additive is preferably 0.1 to 0.3. When the above conditions cannot be met at the same time, the improvement of the high and low temperature comprehensive performance of the above battery cannot be achieved.
[0096] Further comparing Examples 8, 19 with Examples 22, 23, on the basis of the first additive and the second additive satisfying the appropriate dosage, a third additive containing a sulfur-oxygen double bond is further added, which can form a film on the surface of the positive and negative electrodes, and the formed tetravalent or hexavalent high-valent alkyl lithium sulfate can improve the oxidation resistance of the positive electrode interface, and at the same time has high lithium ion conductivity. The third additive and the first additive act synergistically to form an organic-inorganic composite SEI film, especially when the mass ratio of the CN functional groups in the first additive and the second additive is lower than 1.0, the introduction of the third additive can more effectively inhibit the damage of CN to the negative electrode interface and improve the storage and cycle performance of the battery.
[0097] Comparing Examples 19 and 30-34, the use of a fluorinated solvent (DFEA) on the basis of the combined use of the first additive, the second additive and the third additive can further improve the low-temperature discharge performance of the battery while taking into account the cycle performance. However, DFEA has the risk of deteriorating gas production during high-temperature storage. By further using the gas production inhibitor TVS, high and low temperature performance can be effectively taken into account.
[0098] Comparing Example 19 with Comparative Examples 8-9, the first additive, the second additive and the third additive are used in combination, compared with LiDFOB or LiPO 2 F 2 Used in conjunction with the second additive and the third additive, it is more helpful to inhibit gas expansion during long-term storage at high temperatures and reduce the battery safety risk caused by swelling of soft-pack batteries.
[0099] The electrolyte in the formed (0% SOC) lithium cobalt oxide battery cell was obtained by centrifugation, acidified with dilute nitric acid, filtered, and the filtrate was taken. The main components and contents in the electrolyte were measured by gas chromatography-mass spectrometry. The test results are as follows:
[0100] Table 4 Residual amount of additives before and after battery formation and storage
[0101] Recipe Group First Additive HTCN PS Example 1 - Injection volume 0.5% 1% 0% Example 1 - After Formation 0.3% 0.8% 0% Example 1 - After 400 cycles 0.03% 0.5% 0% Example 19 - Injection Volume 0.5% 3% 3% Example 19 - After Formation 0.4% 2.6% 2.2% Example 19 - After 400 cycles 0.25% 2.3% 0.7%
[0102] According to the results in Table 4 above, in the absence of the third additive PS, the first additive and the second additive in Example 1 are gradually consumed as the battery is formed and cycled. It is speculated that the first additive and the second additive participate in the modification of the positive and negative electrode surfaces, respectively, to improve the cycle stability of the high-voltage battery. Compared with Example 1, in Example 19, the content of the second additive is increased to 3% and the third additive PS is introduced. The consumption of the first additive during the cycle is reduced. It is speculated that the second additive and the third additive have a synergistic effect with the first additive, which improves the stability of the electrode interface. Compared with Example 1, it is more helpful to improve the cycle performance of the full battery.
Claims
1. An electrolyte additive composition containing a novel lithium salt, characterized in that: The additive composition comprises: The first additive comprises at least a novel lithium salt having a structure represented by the following formula (I-1): The second additive is selected from the nitrile compound with the structure shown in the following formula (II): In the formula, M1 is selected from -CH, P or -P=O, n is selected from an integer of 0 to 5; R1, R2, and R3 are independently selected from a direct bond, oxygen, -R4-, -O-R4-, or -R5-O-R4-, wherein R4 and R5 are independently selected from C1-C5 alkylene, C2-C5 alkenylene, or C1-C5 alkylene or C2-C5 alkenylene substituted by C1-C3 alkyl or cyano; The mass ratio of the CN functional groups in the first additive to the second additive is 0.03 to 4.
0.
2. The electrolyte additive composition containing a novel lithium salt according to claim 1, characterized in that: The mass ratio of the CN functional groups in the first additive to the second additive is 0.08 to 1.
0.
3. The electrolyte additive composition containing a novel lithium salt according to claim 1 or 2, characterized in that: The first additive further comprises at least one of the compounds represented by the following formulas (I-2), (I-3), (I-4), (I-5), and (I-6): The first additive contains at least 80.0 wt % or more of the novel lithium salt having the structure represented by formula (I-1).
4. The electrolyte additive composition containing a novel lithium salt according to claim 3, characterized in that: The first additive contains 80.0 to 95.0 wt % of the novel lithium salt having the structure represented by the formula (I-1), and the rest is at least one of the compounds (I-2), (I-3), (I-4), (I-5) or (I-6).
5. The electrolyte additive composition containing a novel lithium salt according to claim 1 or 2, characterized in that: In the second additive, M1 is selected from -CH, P or -P=O, n is selected from an integer of 0 to 3; R1, R2, and R3 are independently selected from a direct bond, oxygen, -R4-, -O-R4- or -R5-O-R4-, wherein R4 and R5 are independently selected from C1-C3 alkylene, C2-C3 alkenylene, or C1-C3 alkylene, C2-C3 alkenylene substituted by C1-C3 alkyl or cyano.
6. The electrolyte additive composition containing a novel lithium salt according to claim 5, characterized in that: The second additive is selected from at least one of the nitrile compounds shown in the following structures:
7. A method for preparing an electrolyte, characterized in that: The preparation method comprises: adding a main lithium salt to a non-aqueous solvent until the main lithium salt accounts for 8-20wt% of the total mass of the electrolyte, and then adding the additive composition according to any one of claims 1-6 to obtain an electrolyte, and making the first additive account for 0.01-5.0wt% of the total mass of the electrolyte, and the second additive account for 0.5-10wt% of the total mass of the electrolyte; The non-aqueous solvent is selected from a mixture of cyclic carbonates and linear carbonates and / or linear carboxylates, wherein the cyclic carbonate is selected from at least one of ethylene carbonate, propylene carbonate or fluoroethylene carbonate; the linear carbonate is selected from at least one of dimethyl carbonate, ethyl methyl carbonate, diethyl carbonate or methyl trifluoroethyl carbonate; the linear carboxylate is selected from at least one of ethyl acetate, ethyl propionate, propyl propionate, 2,2-difluoroethyl acetate or 2,2,2-trifluoroethyl acetate, and the amount of any non-aqueous solvent is 0.1-50wt% of the total mass of the electrolyte; The main lithium salt is selected from at least one of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide and lithium bis(trifluoromethylsulfonyl)imide.
8. The method for preparing the electrolyte according to claim 7, characterized in that: The first additive accounts for 0.1-2.0 wt % of the total mass of the electrolyte, and the second additive accounts for 2.0-6.0 wt % of the total mass of the electrolyte.
9. The method for preparing the electrolyte according to claim 7, characterized in that: A third additive is added to the electrolyte, wherein the third additive is selected from at least one of the sulfur-oxygen double bond compounds shown in the following structures, and the amount used accounts for 0.5 to 5.0 wt% of the total mass of the electrolyte:
10. The method for preparing an electrolyte according to any one of claims 7 to 9, characterized in that: A basic additive is added to the electrolyte, wherein the basic additive is selected from at least one of fluoroethylene carbonate, vinylene carbonate, lithium difluorophosphate, lithium tetrafluoroborate, lithium difluorooxalatoborate, lithium difluorobisoxalatophosphate, tris(trimethylsilyl)phosphate, and tris(trimethylsilyl)borate, and any addition amount accounts for 0.1 to 2.0 wt% of the total mass of the electrolyte.
11. The method for preparing the electrolyte according to claim 10, characterized in that: A fourth additive is added to the electrolyte, wherein the fourth additive is selected from at least one of tetravinylsilane, 2,4,6-tri(allyloxy)-1,3,5-triazine, 1,3,5-triallyl isocyanurate, 1,3-dioxane, and 1,4-dioxane, and any addition amount accounts for 0.1 to 2.0 wt% of the total mass of the electrolyte.
12. A lithium-ion secondary battery, comprising a positive electrode sheet, a negative electrode sheet and a separator, characterized in that: The lithium-ion secondary battery is prepared by the following method: the positive electrode sheet, the separator and the negative electrode sheet are wound together into a roll core, sealed with an aluminum-plastic film and then baked, and then the electrolyte prepared by any preparation method described in claims 7-11 is injected therein, and the lithium-ion secondary battery is obtained after standing, forming, volume separation and aging.
13. The lithium-ion secondary battery according to claim 12, characterized in that: The active material of the positive electrode plate is selected from lithium cobalt oxide, lithium nickel manganese oxide, lithium-rich manganese base, lithium manganese oxide, lithium iron phosphate, lithium manganese iron phosphate or LiNi x Co y Mn z L (1-x-y-z) O2, wherein L is Al, Sr, Mg, Ti, Ca, Zr, Zn, Si, W or Fe, 0≤x≤1, 0≤y≤1, 0≤z≤1, 0.5≤x+y+z≤1, and the active material of the negative electrode plate is selected from graphite, silicon carbon or silicon oxygen material.
14. The lithium ion secondary battery according to claim 13, characterized in that: The active material of the positive electrode sheet includes LiCoO2.
15. The lithium ion secondary battery according to claim 14, characterized in that: The cut-off voltage of the lithium-ion secondary battery is ≥4.45V.
16. The lithium ion secondary battery according to claim 15, characterized in that: The electrolyte additive participates in the electrode / electrolyte interface construction during the battery formation process, so that in the electrolyte liquid of the lithium ion secondary battery, the first additive accounts for 0.01-2.0wt% of the total mass of the electrolyte liquid, and the second additive accounts for 0.1-9.0wt% of the total mass of the electrolyte liquid.
17. The lithium ion secondary battery according to claim 16, characterized in that: The third additive accounts for 0.1-4.5 wt % of the total mass of the electrolyte liquid, and the fourth additive accounts for 0.02-1.5 wt % of the total mass of the electrolyte liquid.
Citation Information
Patent Citations
Electrolyte and lithium-ion battery applying electrolyte
CN110148784A
High-energy-density battery electrolyte
CN118173885A
Application of pyrosulfate boron trifluoride composite lithium salt in electrolyte
CN118173890A
Non-aqueous electrolyte of high-voltage lithium ion battery
CN107799822A
Lithium-ion battery electrolyte and lithium-ion battery containing same
CN111029653A
Cited By
Non-aqueous electrolyte and lithium ion battery thereof
CN119812478A
Non-aqueous electrolyte and lithium ion battery thereof
CN119812478B